Mobile Application Development for Robusta Coffee Planting Cycle Mapping and Recording as Part of an Initiative to Revitalize Smart-Agriculture Technology - Anak Agung Surya Pradhana; I Nyoman Darma Kotama (Jurnal Info Sains : Informatika dan Sains, 2023)
Robusta coffee cultivation in Bali's Pupuan District is vital to the Indonesian economy. This study aims to contribute to the improvement of agricultural productivity through the development of a mobile application utilizing geographic information system (GIS) and the collection of robusta coffee cropping cycle data. The purpose of the application is to amass historical data pertaining to various stages of coffee plant development, including fertilization, insect management, and harvesting. By utilizing this application, agricultural practitioners are empowered to enhance the quality of their decision-making regarding the administration of their plantations. The study adhered to a methodical framework, which comprised gathering data, analyzing user requirements, designing the application, and developing it. An application is developed to provide assistance to administrators and producers in various tasks such as crop cycle recording, location setting, and farm management. With any luck, this application will aid in the development of a smart agriculture system in the Pupuan District of Bali and contribute to the enhancement of coffee farming's productivity and efficiency.